New insights into the characteristic skin microorganisms in different grades of acne and different acne sites - Guo, Zitao; Yang, Yuliang; Wu, Qianjie; Liu, Meng; Zhou, Leyuan; Zhang, Liang; Dong, Dake (Frontiers in Microbiology, 2023)
The increasing maturity of sequencing technology provides a convenient approach to studying the role of skin microorganisms in acne pathogenesis. However, there are still too few studies about the skin microbiota of Asian acne patients, especially a lack of detailed analysis of the characteristics of the skin microbiota in the different acne sites. In this study, a total of 34 college students were recruited and divided into the health, mild acne, and severe acne groups. The bacterial and fungal flora of samples were separately detected by 16S and 18S rRNA gene sequencing. The biomarkers of different acne grades and different acne sites (forehead, cheek, chin, torso (including chest and back)) were excavated. Finally, results indicated that there was no significant difference in species diversity between groups. The genera like Propionibacterium, Staphylococcus, Corynebacterium, and Malassezia, which have a relatively high abundance in the skin microbiota and were reported as the most acne-associated microbes, were no obvious differences between groups. On the contrary, the abundance of less reported Gram-negative bacteria (Pseudomonas, Ralstonia, and Pseudidiomarina) and Candida has a significant alteration. Compared with the health group and the mild group, in the severe group, the abundance of Pseudomonas and Ralstonia sharply reduced while that of Pseudidiomarina and Candida remarkably raised. Moreover, different acne sites have different numbers and types of biomarkers. Among the four acne sites, the cheek has the greatest number of biomarkers including Pseudomonas, Ralstonia, Pseudidiomarina, Malassezia, Saccharomyces, and Candida, while no biomarker was observed for the forehead. The network analysis indicated that there might be a competitive relationship between Pseudomonas and Propionibacterium. This study would provide a new insight and theoretical basis for precise and personalized acne microbial therapy.